Ambient storage of microencapsulated Lactobacillus plantarum ST-III by complex coacervation of type-A gelatin and gum arabic. Issue 2 (18th January 2018) - Zhao, Meng; Wang, Ying; Huang, Xue; Gaenzle, Michael; Wu, Zhengjun; Nishinari, Katsuyoshi; Yang, Nan; Fang, Yapeng
Abstract : Sucrose addition and complex coacervation were effective in probiotic protection during ambient storage, which might be correlated with moisture adsorption. Abstract : Ambient storage of dry powdered probiotics is necessary for manufacturer's cost reduction and customer's convenience. Complex coacervation is a promising microencapsulation technique. In this work, a probiotic matrix of type-A gelatin/gum arabic/sucrose (GE/GA/S) with high coacervation pH was designed, based on the alkaline isoelectric point of type-A gelatin. Bacterial survival during ambient storage at room temperature and certain relative humidity were detected. To clarify the protection factors of the coacervation matrix of GE/GA/S, dry microcapsules of GA, GE, GE/sucrose and GE/GA were prepared as controls and compared in terms of their morphology, moisture content, dynamic vapor absorption and cell viability. Probiotics in GE/GA/S5.5 microcapsules behaved the best during spray drying, ambient storage and heat treatment. The results proved that sucrose addition was necessary for cell viability against environmental stresses, and that encapsulation by complex coacervation was a positive factor in cell protection, especially at neutral coacervation pH.